Mali Africa RISING: Agronomic Trials in Bougouni, 2013 - Wageningen University and Research (International Food Policy Research Institute, 2015)
This data study contains data on the village level rangeland biomass measurements. Project title: Mali Africa RISING: Agronomic Trials in Bougouni, 2013. Project abstract: Sustainable intensification of mixed crop livestock systems is a key pathway towards better food security, improved livelihoods and a healthy environment. As part of the US government?s Feed the Future initiative to address hunger and food security issues in sub-Saharan Africa, the US Agency for International Development (USAID) is supporting three multi-stakeholder agricultural research projects to sustainably intensify key African farming systems. Project website: http://africa-rising.net